(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper intends to investigate the causal relationship between teachers’ self-efficacy and teacher teaching practices in Saudi Arabia using Structural Equation Modeling (SEM) based on the public database of the Teaching and Learning International Survey (TALIS 2018). In this study, 2744 teachers responded to the survey, representing lower secondary in mainstream public and private schools in Saudi Arabia. Based on the literature review and the exploratory factor analysis presented in the TALIS 2018 technical report, three constructs represent teacher teaching practices including (clarity of instructional, cognitive activation, and classroom management practices). Teacher self-efficacy includes two constructs (classroom management efficacy and instruction efficacy). After applying structural equation modeling, the main finding indicates a positive influence of teacher self-efficacy on the clarity of instructional practices, cognitive activation practices, and classroom management practices.